Dynamic analysis of high precision construction cable-driven parallel robots. (May 2019) - Ferravante, V.; Riva, E.; Taghavi, M.; Braghin, F.; Bock, T.
Highlights: A dynamic model for cable driven parallel robots is proposed. The model includes position and tension dependent properties of the manipulator. The model has been validated comparing experimental and numerical responses. The response is characterized by structural and cable-induced modes. Abstract: In this paper we propose a modeling strategy for Cable Driven Parallel Robots (CDPRs) that - given their complexity - are typically addressed using simplified analysis, therefore neglecting relevant dynamics. Specifically, the finite element method is used for cables modeling, in order to account for their mass and stress-dependent stiffness. Geometrical effects given by platform motion in the 3D space have been included in our study, coupling cables finite element model and platform dynamic, also mimicking the wrapping of cords around winches. As a result, frequency and time domain responses under harmonic excitation are well captured and, in contrast with other works, the modal analysis revealed system vibrations characterized by local and global modes.